Corn yield response to irrigation level, crop rotation, and irrigation system. Issue 5 (3rd September 2022) - Sorensen, Ronald B.; Lamb, Marshall C.; Butts, Christopher L.
ABSTRACT: Economic sustainability is a result of efficient crop management, irrigation system selection, proper crop rotation, and crop yield. A long-term corn ( Zea mays L.) yield research project was conducted in Southwest Georgia, USA (84°36"W, 30°44"N) during the 2001 to 2018 crop years, which compared four corn crop rotations, three irrigation systems, and three irrigation levels. Drip and overhead irrigation systems, along with a dryland control, were implemented. Drip systems included shallow subsurface drip (S3DI) and subsurface drip irrigation (SSDI). Irrigation levels included dryland, 33%, 50%, 62/66%, and 100% of estimated water use. Crop rotations were 1) peanut ( Arachis hypogaea L.)-corn-corn, 2) peanut-corn, 3) peanut-corn-cotton, ( Gossypium hirsutum L.), and 4) peanut-corn-corn-cotton. There were yield differences due to crop rotation; however, the differences were not consistent across years, irrigation levels, or irrigation systems. The SSDI system had consistently lower yield (9659 kg/ha) than both the S3DI (11, 791 kg/ha) and sprinkler (12, 230 kg/ha) at 100% irrigation level when averaged across all crop rotations and years. In wet years, irrigation level had no effect on yield due to total rainfall amount and timing. However, in dry years, corn yield for sprinkler and SSDI were influenced by irrigation level but not always for S3DI. When selecting an irrigation system, long-term yield should not be the only criterion but should consider crop rotation, system installation cost, field size, irrigation system controls, and irrigation and crop system management.